(3TQM GdehLR (B_ (3ehLR GdbGfhf dGHf GdfajSs - (3LeGd GdOjf eMeO Hf eMeO GdCbUQGFis; (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3hHYO ef LedI eG bQCJg Ydjg ehLR GdbGfhf GdMcje GdYdGeI CHj GdMRe GdbQTi GdeYQha HGHf GdfajS aCQOJ Cf CTQMg deG ajg ef GdeTcdGJ hSejJg HTQM GdehLR , dCfg jMH eG ajg ef GdeTGcd hGdedZR s
(3BNQgG (B:s
(3hjSJMb fGYekG hjSbi ai eGA bOQ edYbI ,hjJOQL Edi CQHYI edGYb hGdeQGO HGdedYbI YfO GdCWHGA ai GdCOhjI eKbGd hGMO , hai GdYSd hGdScQ CQHY eKGbjd , hGddg CYde s
(3HChdgG agQSJ HeG JMJhjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B138 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMji HGTG GdLdjdi (B_ (3GdehUd (B_ (3GdYQGb (B(382) s
Keywords: (3GdWHs